Characteristic of Urinary Tract Stone Patient in Sido Waras General Hospital Mojokerto - Kristian Mohamad Daniputra; Antono Pratanu; Putu Adi Kurniawan (Brawijaya Journal of Urology, 2024)
Objectives. Urinary tract stones have been discovered since the ancient Egyptian period. In the eighteenth century, a Russian scientist, H.C.G von Struve, discovered a struvite stone whose formation was initiated by a urinary tract infection. The prevalence of kidney stone disease in Indonesia was 0,6% in 2013, and in the United States, the incidence of kidney stone disease was 116/100.000 people in 2000. This research aims to determine the characteristics of urinary tract stone patients treated in Sido Waras General Hospital Mojokerto, East Java.Methods. The design of this research is a descriptive study. The inclusion criteria are all new cases of urinary tract stones treated in Sido Waras General Hospital between 2017 and 2018. All clinical data regarding urinary tract stone disease is obtained from medical records retrospectively.Results. There are 285 new cases of urinary tract stones treated in Sido Waras General Hospital Mojokerto in 2 years, in which 236 cases (83%) are male and 49 (17%) are female. Most urinary tract stone patients are classified in the 40-60 age group, with 197 cases in two years. The most common urinary tract stone is kidney stone, with 147 cases (51%). In two years, open surgery is the most common management method for urinary tract stone disease (52%). Based on comorbid disease, there are 120 urinary tract stone patients (42%) suffering from hypertension and 84 urinary tract stone patients (29%) suffering from diabetes mellitus.Conclusions. The incidence of urinary tract stones in Sido Waras General Hospital is 285 cases. Urinary tract stones are more common in males, with a male-to-female ratio of 4:1. Most cases are kidney stones.